MEMBANGUN KULTUR MADRASAH POSITIF MELALUI PRAKTIK KEPEMIMPINAN SERVANT LOVE - Ahmad Khotib; Siti Aimah (As-Sulthan Journal of Education, 2026)
This study aims to analyze the mechanisms and processes of positive culture construction through the practice of "Servant Love" leadership in a madrasah environment. This objective is motivated by the need to unpack the "black box" of social processes linking leadership actions to sustainable cultural change, which has so far remained understudied. The study used a qualitative approach with an intrinsic case study design in one madrasah led by a figure who implements the Servant Love principle. Data were collected through triangulation of passive participant observation techniques, in-depth semi-structured interviews with the madrasah principal, teachers, staff, and students, and analysis of related documents. Data were analyzed interactively and thematically. The results revealed three key mechanisms (1) Operationalization of Servant Love as a "Present-Serving Leader" through physical and emotional presence that builds trust; (2) Transformation of decision-making into a collective learning and empowerment ritual that fosters a sense of agency and we-ness; and (3) Reframing conflict as a momentum for "relationship building" that builds organizational resilience and solidarity. These findings provide a process map showing how micro-practices of love and service-based leadership actually shape the norms, values, and interaction patterns that build a positive madrasah culture.